2020
DOI: 10.1158/2326-6066.cir-19-0493
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Enhances Type I Interferon Responses Downstream of CD47 Blockade, Bridging Innate and Adaptive Immunity

Abstract: Disrupting the binding of CD47 to SIRPa has emerged as a promising immunotherapeutic strategy for advanced cancers by potentiating antibody-dependent cellular phagocytosis (ADCP) of targeted antibodies. Preclinically, CD47/SIRPa blockade induces antitumor activity by increasing the phagocytosis of tumor cells by macrophages and enhancing the cross-presentation of tumor antigens to CD8 þ T cells by dendritic cells; both of these processes are potentiated by CD40 signaling. Here we generated a novel, two-sided f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 51 publications
1
48
0
Order By: Relevance
“…CD40/CD40L interaction partakes in both innate and adaptive anti-tumor immunity via stimulating pro-inflammatory cytokine production, including IL12 and TNF- α, the induction of ADCC, and T cell-mediated immunity and antibody production. It is also currently an active area of investigation for drug development in immune-oncology [ 111 , 112 , 113 ]. In vivo studies of SL-172154 have demonstrated superior anti-tumor activity with the fusion protein over either CD47 antagonist, CD40 agonist antibody as monotherapy or the combination of the two, suggesting a synergistic role [ 110 ].…”
Section: Bispecific Agents Targeting Cd47 and Another Moleculementioning
confidence: 99%
“…CD40/CD40L interaction partakes in both innate and adaptive anti-tumor immunity via stimulating pro-inflammatory cytokine production, including IL12 and TNF- α, the induction of ADCC, and T cell-mediated immunity and antibody production. It is also currently an active area of investigation for drug development in immune-oncology [ 111 , 112 , 113 ]. In vivo studies of SL-172154 have demonstrated superior anti-tumor activity with the fusion protein over either CD47 antagonist, CD40 agonist antibody as monotherapy or the combination of the two, suggesting a synergistic role [ 110 ].…”
Section: Bispecific Agents Targeting Cd47 and Another Moleculementioning
confidence: 99%
“…Previous studies found that SL-172154 significantly improved rejection of both primary and secondary tumors, as compared with individual antibodies targeting CD40 and CD47 used alone or in combination, similar to PD-1-Fc-OX40L ( 56 ). Notably, the safety and efficacy of the bsAb in nonhuman primates in vivo that, the bsAb stimulated dose-dependent elevation in multiple serum cytokines and CD40 + B-cell margination in cynomolgus macaques, without causing hemolysis or thrombocytopenia, provides justification to further explore this strategy in patients with cancers ( 47 ).…”
Section: Bsab Targeting Cd47 and Other Targets That Are Currently In Clinical Trials In Oncologymentioning
confidence: 99%
“…Both these processes are potentiated by CD40 signaling. Accordingly, Schreiber et al developed a SIRPα-Fc-CD40L agonist redirected checkpoint fusion protein to address these distinct pathways with a single biological agent SIRPα-Fc-CD40L is a novel, bifacial fusion protein that combines the extracellular domains of SIRPα and CD40L, adjacent to a fundamental Fc domain [ 70 ]. SIRPα-Fc-CD40L binds CD47 and CD40 with high affinity and activates CD40 signaling without FcR cross-linking.…”
Section: “Don’t Eat Me” Signal Blockade Anti-cd47 Antibody Is An Innate Immune Checkpoint Inhibitormentioning
confidence: 99%